Case Report: Solid variant of papillary thyroid carcinoma in a young adult with Turner syndrome with chronic thyroiditis - Murakami, Daichi; Hijiya, Masayoshi; Iyo, Takuro; Hayata, Sachiko; Ozaki, Takashi; Enomoto, Keisuke; Kono, Masamitsu; Tamagawa, Shunji; Hotomi, Muneki (Frontiers in Oncology, 2023)
Turner syndrome is associated with an increased risk of developing several neoplasms. In particular, a clinical feature of Turner syndrome with chronic thyroiditis implies a relationship with thyroid malignancies. We report a very rare case of solid variant of papillary thyroid carcinoma that was identified during follow-up of chronic thyroiditis in a 22-year-old woman with Turner syndrome. The patient had no notable history of exposure to radiation. No genetic mutations relating to the occurrence of solid variant of papillary thyroid carcinoma including RET/PTC rearrangements, mutations in the BRAF or RAS, were detected by a gene panel test, the Oncomine TM Dx Target test. To our knowledge, this is the first report of a solid variant of papillary thyroid carcinoma in a young adult with Turner syndrome with chronic thyroiditis. Our case suggests that in patients with Turner syndrome there may be different pathogeneses from those previously reported, including exposure to radiation or known genetic mutations for the development of solid variant of papillary thyroid carcinoma.